Pollen tube and root-hair tip growth is disrupted in a mutant of Arabidopsis thaliana. - Schiefelbein, J (1993)
The expansion of both root hairs and pollen tubes occurs by a process known as tip growth. In this report, an Arabidopsis thaliana mutant (tip1) is described that displays defects in both root-hair and pollen-tube growth. The root hairs of the tip1 mutant plants are shorter than those of the wild-type plants and branched at their base. The tip1 pollen-tube growth defect was identified by the aberrant segregation ratio of phenotypically normal to mutant seeds in siliques from self-pollinated, heterozygous plants. Homozygous mutant seeds are not randomly distributed in the siliques, comprising only 14.4% of the total seeds, 5.3% of the seeds from the bottom half, and 2.2% of the seeds from the bottom quarter of the heterozygous siliques. Studies of pollen-tube growth in vivo showed that mutant pollen tubes grow more slowly than wild-type pollen through the transmitting tissue of wild-type flowers. Cosegregation studies indicate that the root-hair and pollen-tube defects are caused by the same genetic lesion. Based on these findings, the TIP1 gene is likely to encode a product involved in a fundamental aspect of tip growth in plant cells.